2012
DOI: 10.3892/ijo.2012.1681
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in follicular cell-derived thyroid carcinomas

Abstract: Abstract. Thyroid carcinoma is the most common malignant endocrine neoplasia. Differentiated thyroid carcinomas (DTCs) represent more than 90% of all thyroid carcinomas and comprise the papillary and follicular thyroid carcinoma subtypes. Anaplastic thyroid carcinomas correspond to less than 1% of all thyroid tumors and can arise de novo or by dedifferentiation of a differentiated tumor. The etiology of DTCs is not fully understood. Several genetic events have been implicated in thyroid tumorigenesis. Point mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 120 publications
1
31
0
2
Order By: Relevance
“…that lead to an aberrant and constitutive activation of MAPK pathway (Romitti et al 2013). BRAF V600E is an oncogenic protein with markedly elevated kinase activity that overactivates the MAPK pathway, especially ERK signaling transduction (Xing 2005, Chakravarty et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…that lead to an aberrant and constitutive activation of MAPK pathway (Romitti et al 2013). BRAF V600E is an oncogenic protein with markedly elevated kinase activity that overactivates the MAPK pathway, especially ERK signaling transduction (Xing 2005, Chakravarty et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of MAPK activation differs in follicular-cell-derived tumours from medullary thyroid cancer. In follicularcell-derived tumours, for example, papillary thyroid cancer, BRAF mutations are often causative (23). In medullary thyroid cancer, MAPK activation is effectuated through the RET mutations (22).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In recent years, molecular biological studies have revealed that the mutation of the genes BRAF and N-RAS is associated with anaplastic transformation (17,18), and conventional cancer chemotherapy has been shifting to molecular-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%